Predicting the effect of headphones on the time to localize a target in an auditory-guided visual search task - Lladó, Pedro; Barumerli, Roberto; Baumgartner, Robert; Majdak, Piotr (Frontiers in Virtual Reality, 2024)
In augmented reality scenarios, headphones obstruct the direct path of the sound to the ears, affecting the users' abilities to localize surrounding sound sources and compromising the immersive experience. Unfortunately, the assessment of the perceptual implications of wearing headphones on localization in ecologically valid scenarios is costly and time-consuming. The availability of tools for automatic assessment of augmented reality gear may boost the quality of the final products and improve the quality of experience of augmented reality applications. Here, we propose a model-based tool for automatic assessment of the acoustic distortion introduced by headphones in terms of the time required to find a target in an auditory-guided visual search task.First, we introduce a score for the degree of degradation for twelve headphones based on the search times obtained with actual listeners. Then, we describe the predictions of the headphoneinduced degradation obtained by an auditory model designed to simulate the listener's search time. The results of the cross-validation procedure show that our tool can predict the degradation score of unseen headphones. This indicates that our tool is able to to automatically assess the impact of headphones on listener experience in augmented reality applications.